Penerapan Cognitive Behavior Therapy (CBT) Dalam Mengurangi Munculnya Physical Symptom Pada Seorang Wanita Dewasa Madya yang Mengalami Hypochondriasis - Riblita Damayanti (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2018)
Abstract . This research was conducted to know the CBT application in reducing physical symptoms in a middle aged adult woman who experienced hypochondriasis. Hypochondriasis is somatoform disorder in which a person is being overwhelmed by the fear of having serious illness. This condition happens repeatedly despite the medical term stated that the patient does not have any physical problem. Thos disorder usually begins in early adolescence and tend to continue. Hypochondriasis often emerge together with anxiety and mood disorder. Especially in middle aged adult women. In that age generally they needs more attention. In middle aged woman often cause changes in social roles. This research uses one female participant who suffers from hypochondriasis. The research was conducted by interview psychological intervention since the beginning of April 2014 until June 2014. The result showed that CBT can reduce the intensity of the emerge of physical symtomps in patient with hypochondriasis.